2001
DOI: 10.1053/ejvs.2001.1406
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy of Intermittent Claudication by Invasive Therapy, Supervised Physical Exercise Training Compared to No Treatment in Unselected Randomised Patients II: One-year Results of Health-related Quality of Life

Abstract: invasive therapy is more effective than supervised training in alleviating illness-specific symptoms and improving certain aspects of physical functioning - the primary HRQL domains impacted on by IC and the principal goals of its treatment. However, since treatment effect sizes were at most moderate and given that untreated claudicants reported at most small deterioration in HRQL, the level of evidence supporting invasive therapy is modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…However, extensive effect on social life and emotional impact has not commonly been documented in the literature. On the contrary, several studies have not been able to demonstrate any significant difference in social isolation or mental health between patients with PAD and controls by using different generic quality of life instruments (Khaira et al, 1996;Breek et al, 2001;Taft et al, 2001). Generic quality of life instruments have a broad application in healthy as well as ill populations and reflect different aspects of emotional and social activities, which are not directly related to health.…”
Section: Discussion Of the Findingsmentioning
confidence: 95%
“…However, extensive effect on social life and emotional impact has not commonly been documented in the literature. On the contrary, several studies have not been able to demonstrate any significant difference in social isolation or mental health between patients with PAD and controls by using different generic quality of life instruments (Khaira et al, 1996;Breek et al, 2001;Taft et al, 2001). Generic quality of life instruments have a broad application in healthy as well as ill populations and reflect different aspects of emotional and social activities, which are not directly related to health.…”
Section: Discussion Of the Findingsmentioning
confidence: 95%
“…Authors confirmed that two publications reported on the same group of patients [7,8]. Therefore the final number of studies was 23, of which five were randomised controlled trials [7][8][9][10][11][12] (see Table 1). …”
Section: Resultsmentioning
confidence: 80%
“…QoL improvements were associated with increases in walking distances in all studies except one [10].…”
Section: Generic Assessment Of Qol Following Participation In Supervimentioning
confidence: 82%
See 2 more Smart Citations